2008
DOI: 10.1007/s10533-008-9205-8
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of effects of sustained decadal precipitation manipulations on soil carbon stocks

Abstract: Throughout a 13 year period, the Throughfall Displacement Experiment sustained both increased (+33; wet) and decreased (¡33%; dry) throughfall into an upland oak forest in Tennessee. Organic (O) horizon carbon (C) stocks were measured at several occasions before, during and after the experiment and mineral soil C stocks before and after the experiment. In the O horizon, higher C stocks were observed in the dry treatment compared to the ambient and wet, attributable to a combination of enhanced litter inputs an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 34 publications
1
7
1
Order By: Relevance
“…From 1993 to 2006, the 12‐year increment of N in long‐lived woody tissue growth was 91 kg N ha −1 . While this rate of vegetation demand is large, it is accommodated by N delivered as wet, dry, and gaseous deposition to the Walker Branch Watershed of approximately 10 kg N ha −1 yr −1 (Hanson et al , 1989; Fröberg et al , in press). Johnson & Todd (1990) estimated leaching rates ranging from 0.4 to 2.0 kg ha −1 yr −1 , which could add no more than 24 kg ha −1 to the total.…”
Section: Discussioncontrasting
confidence: 40%
See 2 more Smart Citations
“…From 1993 to 2006, the 12‐year increment of N in long‐lived woody tissue growth was 91 kg N ha −1 . While this rate of vegetation demand is large, it is accommodated by N delivered as wet, dry, and gaseous deposition to the Walker Branch Watershed of approximately 10 kg N ha −1 yr −1 (Hanson et al , 1989; Fröberg et al , in press). Johnson & Todd (1990) estimated leaching rates ranging from 0.4 to 2.0 kg ha −1 yr −1 , which could add no more than 24 kg ha −1 to the total.…”
Section: Discussioncontrasting
confidence: 40%
“…The increments of K, Ca, and Mg in tree biomass have been estimated 74, 117, and 8 kg ha −1 , respectively, in the TDE plots (Fröberg et al , in press), all of which exceed the observed changes in soil‐exchangeable contents (−27 to +18 kg ha −1 for K, −13 to −94 kg ha −1 for Ca 2+ , and −1 to +17 kg ha −1 for Mg 2+ ; Table 5). In the cases of Ca 2+ and Mg 2+ , weighted average concentrations (and presumably soil contents) did not change significantly, despite the pressures of uptake and leaching, even though concentrations within individual depths did change.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The commonly used facilities to increase temperature in ecosystems include OTC and infrared radiator (Kimball, 2005; Walker et al , 2006). The facilities to alter precipitation include rainout‐shelter and throughfall displacement (Knapp et al , 2002; Fröberg et al , 2008). The next generation of global change experiments may further challenge the facility development by involving new materials, more advanced computer steering, and less environmental impacts.…”
Section: Future Research Programs For Long‐term Global Change Experimmentioning
confidence: 99%
“…While some studies indicated no effect of temperature on SOC [ 2 , 3 ], others observed accelerated decomposition with temperature going up [ 4 7 ], especially in the high-latitude [ 8 , 9 ]. Likewise, the effect of precipitation is also controversial with some reporting precipitation conducive to SOC accumulation [ 10 , 11 ] while others not [ 12 ]. Similar debates also involved other environmental factors such as soil type, texture, pH, N content, vegetation type and land use forms [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%